Comprehensive analysis of grazing intensity impacts alpine grasslands across the Qinghai-Tibetan Plateau: A meta-analysis - Zhang, Zhenchao; Zhao, Yiran; Lin, Hao; Li, Yanpeng; Fu, Jinmin; Wang, Yingxin; Sun, Juan; Zhao, Yanhua (Frontiers in Plant Science, 2023)
Livestock grazing is a dominant practice in alpine grasslands and plays a crucial role in the ecosystem service of the Qinghai-Tibetan Plateau. The effects of grazing on alpine grasslands highly depends on grazing intensity. Up to now, we still lack comprehensive understanding of the general responses of alpine grasslands to different grazing intensities over broad geographic scales across the Qinghai-Tibetan Plateau. Here, we conducted a meta-analysis to explore the responses of plant characteristics and soil properties to grazing intensity in alpine grasslands of the Qinghai-Tibetan Plateau based on 52 peer-reviewed literatures. The results showed that grazing did not change the belowground biomass, while significantly increased the ratio of root to shoot (P < 0.05). Light grazing exhibited no significant effects on the plant richness, Shannon-Wiener diversity, soil water content, soil bulk density, nutrients, microbial biomass carbon, and microbial biomass nitrogen (P > 0.05). Moderate grazing significantly increased the plant richness and Shannon-Wiener diversity, while significantly decreased the soil organic carbon and total nitrogen (P < 0.05). Heavy grazing significantly decreased the plant richness, Shannon-Wiener diversity, water content, soil organic carbon, total nitrogen, microbial biomass carbon, and microbial biomass nitrogen, and significantly increased the soil bulk density (P < 0.05). These findings suggest that overgrazing is closely associated with grassland degradation, and moderate grazing is a sustainable practice to provide animal production and simultaneously maintain ecological functions for alpine grasslands on the Qinghai-Tibetan Plateau.